Influence of protein intake and muscle mass on survival in chronic dialysis patients - Antunes, Aline Araujo [UNESP]; Vannini, Francieli Delatim [UNESP]; Silveira, Liciana Vaz de Arruda [UNESP]; Martin, Luis Cuadrado [UNESP]; Barretti, Pasqual [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP] (Informa Healthcare, 2010)
Introduction: Some studies suggest that high body mass index (BMI) confers survival advantage in dialysis patients, but BMI does not differentiate muscle from fat mass, and the survival advantage conferred by its increase seems to be limited to patients with high muscle mass. Thus, discriminating body components when evaluating nutritional status and survival is highly important. This study evaluated the influence of nutritional parameters on survival in patients on chronic dialysis. Subjects and methods: Anthropometry, bioimpedance, biochemistry, and dietary recall were used to investigate the influence of nutritional parameters on survival in 79 prevalent patients on chronic dialysis. Results: Protein intake <1.2 g/kg/day and creatinine <9.7 mg/dL were independent predictors of mortality in all patients. Regarding dialysis method, protein intake <1.2 g/kg/ day was predictive of mortality among hemodialysis patients, and percent standard mid-arm muscle circumference <80% was identified as a risk factor among peritoneal dialysis patients. Conclusion: Higher muscle mass, possibly favored by a higher protein intake, conferred survival advantage in dialysis patients.
Keywords: dialysis; malnutrition; mortality; muscle mass; protein intake; survival